A STUDY ON THE VOCABULARY EDUCATION APPLYING THE POLYSEMY (European Journal of Interdisciplinary Research and Development, 2025)
The purpose of this paper is to teach vocabulary to foreign learners of Korean in an effective way, so that they can remember it for a long time and use it appropriately for communication as well as reading and writing. In other words it seeks the method by which students study vocabulary easily, interestingly, and effectively; and how they can remember over the long term the vocabulary that they've studied. At first, it tried to search for a vocabulary instruction method within the theory of vocabulary teaching method where theoretical background is necessary for vocabulary learning. It also presented the necessity of vocabulary learning by the meaning relation on the basis of preceeding research on the characteristic of Korean vocabulary and the vocabulary teaching method. Through the previous educational experience, the most preferred vocabulary learning method for learners overall was learning vocabulary based on vocabulary features such as synonyms, antonyms, and polysemy that have semantic relationships between words. Based on these results, this paper focused on the lexical relationship using polysemy and examined its characteristics. First, the concept of polysemy and its characteristics were examined, and then, through the analysis, different teaching methods were established for each type, and a vocabulary learning model using polysemy was presented.